The Development of Training of Extracurricular Power toward Volley Ball Men Players at Junior High School 2 Koto Baru Kabupaten Dharmasraya - Dwipa Suji Harsoni; Zuhar Ricky; Maldin Ahmad Burhan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
This research is motivated by players who have explosive leg muscles in the poor category, because extracurricular volleyball players at SMP 2 Koto Baru have never held a special program that focuses on physical exercise, especially on the players' leg muscles, but only focuses on on technical training. This can be seen through the temporary test results obtained through the smash jump test. In ongoing extracurricular activities, researchers saw when players did volleyball exercises where the player when making a jump still had a low jump, so that he had difficulty in smashing. Seeing these conditions, how important is the explosive power of leg muscles in volleyball. To improve the physical condition, an exercise that is in accordance with the dominant exercise in training the leg muscles is needed. This type of research is research & development or Research and Development (R&D). The model development uses the ADDIE model which consists of 5 stages, namely analysis, design, development and evaluation. The five stages were carried out by analyzing the needs of students. Then the validation test by 3 validators (expert team), practicality test by the PJOK teacher, after the model is categorized as valid and practical, then the effectiveness test is carried out by 10 players by doing a smash jump test. The results of the research on the development of the exercise model taught by the volleyball leg muscle training model in the validity test obtained percentage data with an average of 82.22% categorized as very valid, the practicality test by PJOK teachers with a percentage of 96% and players with a percentage of 78.4% categorized as practical. , while the effectiveness test with a percentage of 90% is categorized as very effective. Based on the results obtained, the volleyball leg muscle training model is categorized as valid, practical and effective, so it can be concluded that the volleyball leg muscle training model can be applied.